PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL PERFORMANCE PERUSAHAN (STUDI PADA BANK YANG MASUK DALAM PERINGKAT 10 BESAR CGPI TAHUN 2008-2010) - HADI SANTOSO, GESANG Hadi (Jurnal Akuntansi AKUNESA, 2013)
The Purpose of this research is to examine the effect between corporategovernance implementation quality and corporate financial performance.Samples of this research is banking companies which include the top ten of CGPI(Corporate governance Perception Index) score in 2008, 2009 and 2010 with 10companies as samples. A measure of corporate governance implementationquality is CGPI score. A measure of financial performance is ROA, ROE, NIM,BOPO, and LDR. Result of regression analysis shows significantly there are effectbetween CGPI score and ROA, ROE, and BOPO. It means that there are effectbetween corporate governance quality and financial performance.Keywords: corporate governance, financial performance, CGPI